Pain during Endometrial Sampling between Menstrual Regulator and Standard Uterine Curette - Angsuwathana, Surasak; Hosuwan, Tanaboon (Siriraj Medical Journal, 2004)
This study was designed to compare the level of pain of patients during endometrial sampling, using a menstrual regulator and a standard uterine curette. A randomized single-blind clinical trial was conducted on eighty women who had abnormal uterine bleeding and needed diagnostic fractional curettage at the Department of Obstetrics and Gynecology, Faculty of Medicine Siriraj Hospital. They were randomly assigned to two groups. The uterine curettage was performed using a menstrual regulator in the first group and a standard curette in the second group. The pain scores before, during and after the curettage procedure were determined by a visual analogue scale. The time for the procedure was observed and the tissue was sent for pathological evaluation. The median pain scores during and 30 minutes after the procedure were lower in the menstrual regulator group compared to those in the standard curette group (p<0.05). The time in the menstrual regulator group was shorter (p<0.05) and the quality of tissue for diagnosis was better (p<0.05) than in the standard curette group. No serious complications were observed between both groups. Using a menstrual regulator for endometrial sampling can significantly reduce the pain, is easier to perform and yields better tissue tissue quality compared to the standard curette.